Role of Corticosteroid in Reducing Post Operative Complication Following Extraction of Impacted Mandibular Third Molar - Khan, Yahya; Khan Tareen, Mirza; Hussain, Mushahid; Muhammad Ammar; Siddique Ullah; Muhammad Bilal (Indus Journal of Bioscience Research, 2025)
Maxillofacial surgery, one of the most commonly performed surgeries in oral and maxillofacial surgery, was the surgical removal of impacted third molars of the mandible. Although it was routine, it was often linked to postoperative complications (e.g., pain, swelling, trismus, difficulty with mastication, and dry socket) because of the postoperative inflammatory response. The use of corticosteroids has been extensively applied in reducing postoperative morbidity, but its use did not flourish because of a lack of local evidence of its efficacy. This research aimed at establishing the prevalence of postoperative complications among patients who used corticosteroids after the extraction of impacted mandibular third molars. This was a five-month period, cross-sectional and descriptive study in the oral and maxillofacial department of sandeman provincial hospital Quetta during the period from January 2025 to May 2025. Non-probability consecutive sampling was used to select 252 patients aged 18-65 years who had surgical exodontomy of affected third molars of the mandible. Individuals were excluded who had systemic disease, immunocompromised status, renal or liver impairment, coagulopathy, or pregnancy. All operations were done by one experienced operator using a standardized procedure. In the postoperative period, 4 mg IV corticosteroid, standard analgesics, and antibiotics were used for all patients. The complications assessed on postoperative day 1, 3, and 7 were pain (VAS >3), trismus (<35 mm mouth opening), dry socket, and mastication issues. The data were entered into a structured proforma and evaluated with SPSS version 25. The qualitative variables were presented in the form of frequencies and percentages, and quantitative variables were presented in the form of mean (SD) or median (IQR). Effect modifiers were controlled through stratification, and chi-square/Fisher’s exact tests were executed with a significance of p ≤ 0.05. The study demonstrated that there was a quantifiable decrease in postoperative complications in patients taking corticosteroids, which means that the levels of pain, trismus, mastication, and difficulty with dry sockets decreased in comparison to the previous instances of complication rates in the same groups. The use of corticosteroids was found to be effective in reducing postoperative complications following the extraction of impacted mandibular third molars. The findings provided valuable local evidence and supported the rational and evidence-based use of corticosteroids to improve postoperative recovery and patient comfort.